The cost of the food we waste: how to change behaviours? - Aheeyar, Mohamed M. M.; Drechsel, Pay (2022)
For food-wasting stakeholders to understand the benefits of waste reduction, the quantification of food waste in order to identify its lost financial value and hot spots for interventions are crucial.